Творческая история «Краткого руководства к красноречию» М. В. Ломоносова в свете компиляционных источников: Новые материалы [A Creative History of Mikhail Lomonosov’s “Kratkoe rukovodstvok krasnorechiiu” in Light of Some Compilations: New Perspectives] - Andrei Kostin (Slavica Revalensia)
It is a matter of common knowledge that European scholarship of the Early Modern period was grounded in compilations. Mikhail Lomonosov’s studies in rhetoric is an example of such practice. It is established that he relied on such sources as De eloquentia sacra et humana (1617) by Nicolas Caussin, (Novus) candidatus Rhetoricae (1659) by François Pomey, and Ausführliche Redekunst (1736) by Johann Christoph Gottsched. This article by Andrei Kostin provides a detailed analysis of the second version of Lomonosov’s Kratkoe rukovodstvo k krasnorechiiu (1748) vis-à-vis two popular manuals on rhetoric: Palaestra oratoria (1659) by Jacob Masen, and Commentariorum rhetoricorum libri VI (1606) by Gerhard Johann Vossius.